Decision Support System of the Employees Acceptance using Analytical Hierarchy Process (AHP) and Multi Factor Evaluation Process (MFEP) - Maricar, M. Azman; Wahyudin, Wahyudin; Sudarma, Made (International Journal of Engineering and Emerging Technology; Vol 1 No 1 (2016): July - December, 2017)
In every company always need new employees of the younger and potentially. The Program management trainees intended to seek a superior candidate according to the assessment of the company, where later on the presidential candidates who passed the final selection will be given training and education about the management in general. And expected from the program management trainees are able to create a new generation with the soul of the leadership of the high. Decision support system is used to help the decision makers in determining the presidential candidates are eligible to participate in the education and training program management trainees, from five candidates are the only two candidates who received. The criteria and the weight of the specified is interview (0,558), the writ ing test (0,122), ps ycho tes t (0,263), and health test (0,057). The method used is Multi Factor Evaluation Process (MFEP) and Analytical Hierarchy Process (AHP). Both methods to get the same result namely candidates 2 and 4 candidates are entitled to received from the selection process. For the calculation of the consistency ratio is not there is a value criteria above 0.1 (which is specified by Saaty).